Perlindungan Lingkungan dalam Hukum Humaniter - Sri Wartini (Fakultas Hukum Universitas Islam Indonesia, 2003)
War has never been kind to human environment and human health. Trough out history, warfare hasbeen associated with death, disease, pollution and destruction of the environmentThe Human Rights Law and Humanitarian Law does not protect the Environment directly, so that the protection of those isstill weak